2022
DOI: 10.51542/ijscia.v3i4.33
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Fermented Banana Stem as Corn Substitutes on Performance and Protein Utilization in Growing-Finishing Pigs

Abstract: The objective of this study was to test banana stem silage as a substitute for corn on the performance and protein utilization rate of Duroc crosses pigs in the rearing phase. A total of 12 Duroc crosses pigs in the rearing phase with an average initial weight of 51.25 kg (KV = 7.02%). A completely randomized design (CRD) with 4 treatments and 3 replicates was used in this study. The treatments were T0: ration without a mixture of fermented banana stems (FBS), T1: ration with 5% FBS instead of cornmeal, T2: ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
1
1
0
Order By: Relevance
“…This means that, up to 20% of BP can be fed to growing/ finishing pigs without any adverse effects on growth performance and FCR. Our reports are consistent with other works performed by Dhema et al (2022) andTheit et al (2022) in growing finishing pigs, that reported a gradual decrease in both ADG and FCR when incorporation level of BP increases in the ration. Substituting maize on an equal weight basis with banana stem might result in overestimation of energy value of banana meal with negative effects on growth performance.…”
Section: Growth Performancesupporting
confidence: 93%
“…This means that, up to 20% of BP can be fed to growing/ finishing pigs without any adverse effects on growth performance and FCR. Our reports are consistent with other works performed by Dhema et al (2022) andTheit et al (2022) in growing finishing pigs, that reported a gradual decrease in both ADG and FCR when incorporation level of BP increases in the ration. Substituting maize on an equal weight basis with banana stem might result in overestimation of energy value of banana meal with negative effects on growth performance.…”
Section: Growth Performancesupporting
confidence: 93%
“…Complete feeding also does not provide an opportunity for livestock to choose the feed provided as is the case with conventional feeding where forage feed is given separately with concentrate feed. Several studies on complete feeding with mixed agricultural waste in the form of coarse flour and fine flour in goats have been shown to be able to increase the palatability of livestock [8,9]. In addition, the high CFi nana stem cannot be given directly to pigs because it will reduce the digestibility value.…”
Section: Introductionmentioning
confidence: 99%